Dampak Subsidi Pupuk Terhadap Petani Kecamatan Simpur Kabupaten Hulu Sungai Selatan - Maulina Ayu Lestari; Lina Suherty; Chairul Sa’roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to analyze (1)  How is the role of fertilizer subsidies in increasing farmer production ; (2) Is there a difference in income for farmers before using subsidized fertilizers.The research respondents were 72 farmers in Simpur, Hulu Sungai Selatan, which can be used in data processing. Data were processed using Paired Sample T-test using SPSS application version 26.The results of this study indicate that the measurement of the implementation of fertilizer subsidy distribution is very effective because it can increase farmers 'incomes, so that farmers' lives are more prosperous. In addition, the existence of fertilizer subsidies has greatly helped farmers in Simpur District, Hulu Sungai Selatan to increase the production of agricultural commodities so that they can support national food security. The income of farmers who before using fertilizer subsidies looks significantly different.Keywords: Subsidized Fertilizer,Farmer Production, Farmer Income.